Laboratory for liberty : the South Carolina legislative committee system, 1719-1776. - Frakes, George Edward, 1932- (University Press of Kentucky, 1970)
This comprehensive study highlights the importance of legislative and extralegal committees in the political and institutional development of early American history, showing how the colonial experience modified a basic British institution, using it in the cause of legislative supremacy and, eventually, independence. The book illuminates the role played by committees in the growth of colonial self-government, tracing the committee system to its origins in the parliamentary committees of medieval England, then following the permutations of the committee system through the decades in which sel.